Comparison of Shoe-surface Tractions on Various Playing Surfaces in Futsal. (2015) - Keshvari, Bahador; Senner, Veit
Abstract: Futsal is a small version of football, which is played in over 100 countries. The smaller pitch of futsal causes players to perform multiple activities in several times such as sprinting, walking, running, jumping, cutting and so on. Consequently, the risks of non-contact injuries are increasing. One of the factors can influence the risks is a shoe-surface traction. The Current research is aimed at comparing the traction between futsal shoe and four different playing surfaces. In the first part of the experimental test, cutting maneuver as a critical activity was performed by former Bayern Munich Player, Mr. Timo Heinze. A force plate and two high speed cameras were prepared to collect forces (Fx, Fy and FZ ) and angles during cutting maneuver. In the second part, a device, traction tester was considered in order to simulate the certain activity, which was reconciled with the force and angle of the subject. Accordingly, the traction between futsal shoe (Joma Top Flex 301 Sala) and four samples (Snap Sport (Shock Tower), Descol (Pulastic Outdoor), Green Tower and Snap Sport (Bounce Back)) were measured. The activity classified into two traction phases, translation and rotation. T-test results show that there are significant differences between translational traction (T T ) and rotational traction (T R ) in three samples (Snap Sport Bounce Back, Green tower and Descol) . They are 0.0019, 0.0001, 0.012 respectively (P-value<0.05). The mean of three trials of tractions determined that greater translational tractions (Phase1) are associated lower rotational traction (Phase 2). To avoid foot fixation and ACL injuries in phase 2, a greater rate ofT R thanT T is necessary. The Snap Sport (Bounce Back) showed the higher level of translational coefficient (0.2007) and a safe range of rotational coefficient (0.0647) . It was considered as an appropriate playing surface among other samples.